2016
DOI: 10.1039/c6nr03459d
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanorod@silica-carbon dots as multifunctional phototheranostics for fluorescence and photoacoustic imaging-guided synergistic photodynamic/photothermal therapy

Abstract: Phototheranostics, which is the application of light in the diagnostic imaging and therapy of cancer, has shown great promise for multimodal cancer imaging and effective therapy. Herein, we developed multifunctional gold nanorod@silica-carbon dots (GNR@SiO2-CDs) as a phototheranostic agent by incorporating carbon dots (CDs) with gold nanorods (GNRs), using SiO2 as a scaffold. In GNR@SiO2-CDs, the GNRs act as both photoacoustic (PA) imaging and photothermal therapy (PTT) agents, and the CDs serve as fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(75 citation statements)
references
References 66 publications
1
74
0
Order By: Relevance
“…The combination of PDT and PTT proved to be more efficient to kill cancer cells. [150] (Continued.) complexes, which chemically bonded on the CDs surface.…”
Section: Mcf-7 Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of PDT and PTT proved to be more efficient to kill cancer cells. [150] (Continued.) complexes, which chemically bonded on the CDs surface.…”
Section: Mcf-7 Cellsmentioning
confidence: 99%
“…Gold nanorods also exhibit excellent photothermal behaviors with the potential of serving as PTT and photoacoustic (PA) agent. Jia et al [150] constructed a photo theragnostic agent based on gold nanorod@SiO 2 -CDs by introducing a thin layer of SiO 2 between Au nanorods and CDs ( figure 11). The SiO 2 layer has two functions: improving the stability of the Au nanorods and avoiding the fluorescence quenching of CDs.…”
Section: Fluorescent Cds Conjugated With Photothermal Therapeutic (Ptmentioning
confidence: 99%
See 1 more Smart Citation
“…An umber of recent studies have successfully reported the use of these carbogenic nanostructures as dual-mode imaging and PDT agents, mostly referred to graphene-like dots or functionalized nanodiamonds. [1,4,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Herein, we report the use of CNDs synthesized by the hydrothermal carbonization (HTC) of ethylenediaminetetraacetic acid (EDTA) at 260 8C( see Experimental Sectionf or furtherd etails). Thism olecular precursorh as been selected to induce the direct generation of nitrogen-doped carbon nanodots (N-CNDs) in as ingle step without the need for secondary amine co-reactants.…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission [167]. B) Schematic illustration of GNR@SiO 2 -CDs nanocomplex applications in PA imaging, PTT, and PDT for cancer treatment.…”
mentioning
confidence: 99%